
计算与化简:(1)(?2)÷[(?12)2×(12)3]×|?254|?(?5);(2)已知a=1,b=2,c=12,计算2a-3b-[3abc-(2b
计算与化简:(1)(?2)÷[(?12)2×(12)3]×|?254|?(?5);(2)已知a=1,b=2,c=12,计算2a-3b-[3abc-(2b-a)]+2abc...
计算与化简:(1)(?2)÷[(?12)2×(12)3]×|?254|?(?5);(2)已知a=1,b=2,c=12,计算2a-3b-[3abc-(2b-a)]+2abc的值.
展开
1个回答
展开全部
(1)(-2)÷[(-
)2×(
)3]×|-
|-(-5)
=(-2)÷(
×
)×
+5
=(-2)×32×
+5
=-395.
(2)2a-3b-[3abc-(2b-a)]+2abc
=2a-3b-3abc+2b-a+2abc
=a-b-abc;
把a=1,b=2,c=
代入,
原式=1-2-1×2×
=-2.
1 |
2 |
1 |
2 |
25 |
4 |
=(-2)÷(
1 |
4 |
1 |
8 |
25 |
4 |
=(-2)×32×
25 |
4 |
=-395.
(2)2a-3b-[3abc-(2b-a)]+2abc
=2a-3b-3abc+2b-a+2abc
=a-b-abc;
把a=1,b=2,c=
1 |
2 |
原式=1-2-1×2×
1 |
2 |
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询